An Analysis of 16 Channel 64 User Hybrid WDM/TDM Topology in the Optiwave Simulation Environment - Dar, Aasif Bashir; Zahoor, Furqan; Jha, Rakesh Kumar; Tripathi, Neeraj; Sabraj, Manish (International Journal of Computer Sciences and Engineering, 2025)
The aim of the present work is to demonstrate the concept of a packet- interleaved WDM system i.e; hybrid optical access network, which serve as the important candidate of next generation access networks. The entire network topology design was simulated in the OPTIWAVE development environment, consisting of transmitter, channel and receiver section. Each section is elaborated, while the analysis of measured values from topology is presented in the last part of the article.